Targeting the Beast Along My Illness Trajectory: A Qualitative Study of Females With Triple-Negative Breast Cancer - Josianne Scerri PhD; Janice Agius MSc (Mental Health Nursing); Michael Galea PhD (Journal of Patient Experience)
Breast cancer subtypes differ in prevalence, aggressiveness, and availability of targeted therapies. However, research often examines the lived experiences of individuals with breast cancer collectively. One subtype, Triple-Negative Breast Cancer (TNBC) is an aggressive form of cancer that lacks targeted therapy and has higher recurrence and mortality rates. This study aims to explore the lived experiences of individuals diagnosed with TNBC, from diagnosis through active treatment. Audio-recorded interviews were conducted with 11 women who had completed treatment for TNBC. Ages ranged between 26 and 63 years. Data collected were analyzed using interpretative phenomenological analysis. Four group experiential themes were extracted: “Living in shellshock,” “Fighting the aggressive beast,” “Pulling out the beast,” and “Facing the unknown.” Participants described substantial emotional distress stemming from the aggressive progression of TNBC and its earlier onset. The rarity of TNBC further intensified perceptions of reduced survival odds. This study underscores the importance of comprehensive care for TNBC patients, incorporating ongoing engagement with TNBC survivors, access to mental health services, and inclusive screening that includes younger women.